Transition to motherhood for Japanese primiparas from delivery to 6 months postpartum: A qualitative study - Youko Katou; Mitsuko Okamura; Mitsuko Ohira (Wiley, 2022)
Abstract Aim This study investigates aspects of the socio‐culturally influenced Japanese primiparas' transition to motherhood. Design A qualitative descriptive study approach with interviews of Japanese primiparas was used. Methods Individual interviews with 21 Japanese primiparas were conducted, with a focus on their transition to motherhood and familiarization with the maternal role. The interviews were analysed, and categories and subcategories were established. This paper was developed using the COREQ guidelines for reporting qualitative studies. Results Seven major categories with 26 subcategories were identified in the transition to motherhood. The seven categories are listed as follows: "confusion with first childcare experience," "suffering related to childcare," "clinging to the image of an ideal mother," "internal conflict while comparing oneself to other mothers," "undertaking childcare by disengaging from one's stereotype," "realization of becoming a mother" and "changing relationship with surrounding people."